Overcoming Speech Disability In Tom Hooper's The King's Speech Movie (2010): An Existentialist Approach - Astuti, Budi (2012)
The research is proposed to analyze the Overcoming Speech Disability in The King's Speech movie by Existentialist Approach. The research sets two objectives: the first is to analyze the movie in term of structural elements, and the second is to analyze the movie based on the existentialist approach. This study is qualitative study using the Movie of The King's Speech as the object of the study. There are two kinds of data source: primary and secondary. The primary data source is the play of the movie The King's Speech directed by Tom Hooper and the secondary data source is the other data related to the research, such as books of existentialist approach theory, movie script, commentaries, internet and other relevant information. The method of collecting data in the research is Watching the movie several time, Taking notes of important part in both primary and secondary data, Determining the major character, Arranging the data into several part based on it classification, Analyzing the data based on Existentialist Approach theory, Drawing conclusion based on the analysis of the data. In analyzing the data, the writer employs descriptive analysis. The study comes to the following conclusions. Based on the existentialist analysis, it is evident that in The King's Speech movie, the director illustrates an overcoming speech disability of the King George VI. Tom Hooper reflects how to overcome speech disability for making dream into reality